2015
DOI: 10.1212/wnl.0000000000001336
|View full text |Cite
|
Sign up to set email alerts
|

Measuring quality of life in muscular dystrophy

Abstract: Additional scale development research is needed to enhance assessment of QOL for individuals with MD. Item banking and computerized adaptive assessment would be particularly beneficial by allowing the scale to be tailored to each individual, thereby minimizing respondent burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 36 publications
(66 reference statements)
1
33
0
Order By: Relevance
“…HRQoL entails multiple dimensions including physical, psychological, and social function. Factors associated with reduced HRQoL in muscular dystrophies include older age, longer disease duration, greater disease severity, and depressed mood . Although several studies have used dysphagia‐specific QoL measures in OPMD, there have been no studies of overall HRQoL and its determinants in a purely OPMD population.…”
mentioning
confidence: 99%
“…HRQoL entails multiple dimensions including physical, psychological, and social function. Factors associated with reduced HRQoL in muscular dystrophies include older age, longer disease duration, greater disease severity, and depressed mood . Although several studies have used dysphagia‐specific QoL measures in OPMD, there have been no studies of overall HRQoL and its determinants in a purely OPMD population.…”
mentioning
confidence: 99%
“…Individuals living with NMD do not perceive physical ability as important in the physical domain of QoL; ease of mobility, vitality, pain and fatigue were identified as more important 55 . These components are captured in the French VSP-A measure utilised by Vuillerot et al 53 , who compared QoL in youth with NMD amongst each other grouped by physical ability.…”
Section: Physical Wellbeing Domains Of Qolmentioning
confidence: 97%
“…Notwithstanding, our checklist identified a need for clearer reporting of recruitment strategies, methods that recruit greater participant numbers and use of age and population validated QoL measures 55 .…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 The complex nature of DM1 results in various levels of disability, and for many, reduced social participation and independence. 15,16 Although the findings regarding HRQoL in DM1 have been diverging, several studies have found reduced HRQoL. 3 International research programmes such as OPTIMISTIC have emerged, aiming to improve clinical practice and quality-of-life standards in the DM1 population.…”
Section: Introductionmentioning
confidence: 99%